Water Sensitive Urban Design – Principles and Inspiration for Sustainable Stormwater Management in the City of the Future - Suwanarit, Asan (Journal of Architectural/Planning Research and Studies (JARS), 2018)
One of the essential challenges of contemporary sustainable design is to allow humans and nature to coexist in mutual respect, combining the best aspects of the built landscape with the dynamism and beauty of the environment. Integrating the functionality of stormwater management with urban and landscape design is, therefore, a good example.